PERAN SEKOLAH DALAM MENANAMKAN SIKAP GOTONG ROYONG PADA SISWA KELAS VII - Muhammad Jerico Arriza; Bachrul Ulum (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2026)
This study aims to analyze the forms of activities and school strategies in instilling a spirit of mutual cooperation in seventh-grade students at Al-Fattahiyyah Islamic Junior High School Ngranti Boyolangu Tulungagung, and to identify supporting and inhibiting factors that hinder the process. The lack of social awareness and the presence of individualistic tendencies in the transition phase of early adolescence apply the importance of optimizing the role of formal institutions institutionally. The method used in this study is descriptive qualitative. Data collection was carried out through undercover participant observation, semi-structured interviews with the principal, Pancasila Education teachers, homeroom teachers, and students, as well as documentation studies. Technical data analysis includes data condensation, extraction, data presentation, and drawing conclusions. Checking the validity of the data was carried out through increased diligence, triangulation of sources and techniques, and member checking. The research results indicate that the school's strategy is implemented holistically through four aspects: the integration of collaborative learning in the classroom (group work and presentation methods), habituation program activities (daily duty and periodic community service), the development of a school culture based on the values ​​of togetherness and Islamic brotherhood, and the concrete role models of teachers. Key supporting factors include a conducive Islamic boarding school environment, teacher commitment, and the synchronization of Islamic values ​​and Pancasila. Meanwhile, inhibiting factors include the residual individualistic ego of some students, the negative impact of gadget use outside of school, and a lack of consistent discipline. The implications of this research emphasize the importance of strengthening integrated social character from an early age in junior high school. ABSTRAK Penelitian ini bertujuan untuk menganalisis bentuk kegiatan dan strategi sekolah dalam menanamkan sikap gotong royong pada siswa kelas VII di SMP Islam Al-Fattahiyyah Ngranti Boyolangu Tulungagung, serta mengidentifikasi faktor pendukung dan penghambat yang dihadapi dalam proses tersebut. Kurangnya kepedulian sosial dan adanya kecenderungan individualistis pada fase transisi remaja awal mendasari pentingnya optimalisasi peran lembaga formal secara institusional. Metode yang digunakan dalam penelitian ini adalah kualitatif deskriptif. Pengumpulan data dilakukan melalui observasi partisipatif tersamar, wawancara semi-terstruktur dengan kepala sekolah, guru Pendidikan Pancasila, wali kelas, dan siswa, serta studi dokumentasi. Teknis analisis data meliputi kondensasi data, penyarian, penyajian data, dan penarikan kesimpulan. Pengecekan keabsahan data dilakukan melalui peningkatan ketekunan, triangulasi sumber dan teknik, serta member check. Hasil penelitian menunjukkan bahwa strategi sekolah diwujudkan secara holistik melalui empat aspek: integrasi pembelajaran kolaboratif di kelas (metode kerja kelompok dan presentasi), program kegiatan pembiasaan (piket harian dan kerja bakti berkala), pengembangan budaya sekolah berlandaskan nilai kebersamaan serta ukhuwah Islamiyah, dan keteladanan nyata dari para guru. Faktor pendukung utama meliputi lingkungan sekolah berbasis pesantren yang kondusif, komitmen guru, serta sinkronisasi nilai keislaman dan Pancasila. Sedangkan faktor penghambat mencakup sisa ego individualistis sebagian siswa, dampak negatif penggunaan gadget di luar sekolah, dan kurangnya disiplin konsisten. Implikasi penelitian menegaskan pentingnya penguatan karakter sosial terintegrasi sejak dini di jenjang sekolah menengah pertama.